2021
DOI: 10.7759/cureus.13208
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Infectious Mortality at the End of Induction Chemotherapy in Acute Lymphoblastic Leukemia and Lymphoma Patients: Findings From a Tertiary Care Cancer Center

Abstract: Background and objective In low-and low-to-middle-income countries (LMICs), the incidence of treatment-related mortality (TRM) in patients with acute lymphoblastic leukemia (ALL) and lymphoblastic lymphoma (LBL) is up to 52%. This study aimed to determine the mortality rate at the end of the induction phase of the treatment among patients with ALL and lymphoma at a tertiary care cancer center. Methods This retrospective study analyzed outcomes after induction chemotherapy in pediatric patients with acute leuke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
2
0
4
Order By: Relevance
“…), Rabia et al (2021) reported 10 % death in ALL patients during the course of induction chemotherapy in a tertiary care cancer hospital 8. This study states, sepsis occurred in 76.6% patients (46/60).…”
mentioning
confidence: 72%
“…), Rabia et al (2021) reported 10 % death in ALL patients during the course of induction chemotherapy in a tertiary care cancer hospital 8. This study states, sepsis occurred in 76.6% patients (46/60).…”
mentioning
confidence: 72%
“…Кроме этого, следует отме тить и высокий процент неотложных состояний на момент обращения, прежде всего обусловленных раз витием гиперлейкоцитоза,среди прочего может сви детельствовать о поздней диагностике основного за болевания. Адекватный объем противомикробной, инфузионной, гемотрансфузионной терапии, а также контроль над СОЛО и возможными электролитными нарушениями будут являться ключевыми факторами прогноза на инициальном этапе ведения пациентов с ОЛ [6,27].…”
Section: Discussionunclassified
“…Цитотоксическое, миелосупрессивное и иммуно супрессивное действия противоопухолевых препаратов в периоде ИХТ являются причинными факторами развития бактериальных и грибковых инфекций [6,27]. Следует отметить, что и нарушение барьерной функции кожи и слизистых оболочек, в первую очередь желудочнокишечного тракта, будет определять риски транслокации эндогенной флоры с развитием тяжелых инфекционновоспалительных заболеваний [28].…”
Section: Discussionunclassified
“…Многократные госпитализации больного в хирургические и терапевтические стационары и ОРИТ привели к присоединению полирезистентной микрофлоры, персистенция которой неизбежно влечет летальный исход в постхимиотерапевтическом периоде. Приведенный клинический пример больного Г. подтверждает мировые данные о необходимости как ранней диагностики лимфом, так и недопустимости длительного нахождения пациента на диагностическом этапе в различных отделениях стационара [8,9].…”
Section: Discussionunclassified